PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Albino Da Cruz Dos Santos, 12.05.52.0051; Maryono, Maryono (Students Journal of Accounting and Banking, 2018)
This study aims to determine the Influence of Financial Performance on Stock Returns on Manufacturing Companies Available In Indonesia Stock Exchange. The population in this study is a manufacturing company listed on the stock exchange Indonesia in 2013-2015. The sample in this research is taken with Purposive Sampling method. Data were analyzed by using Independent sample ttest. In Return On Asset variable obtained significant value. This means Return On Asset variable. statistically have a significant positive effect on stock Return. In Return On Equity variable obtained significant. This means the Return On Equity variable statistically significant positive effect on stock Return. In Economic Value Added variable obtained significant. This means Economic Value Added variables are statistically significant positive effect on stock Return. In the Debt to Equity Ratio variable obtained significant. This means that the Debt to Equity Ratio variable is statistically significant positive effect on stock Return.Keywords: ROA, ROE, EVA, DER Return shares